KELAMBATAN WAKTU PENYALAAN CAMPURAN SOLAR DAN METIL ESTER KELAPA SAWIT PADA MOTOR DIESEL INJEKSI LANGSUNG - Prawoto L; Shalahuddin Shalahuddin; R. C Nugroho (Mesin, 2004)
Ignition delay is an important parameter in diesel engine operation. It is defined as the time (or crank angle degree) between the start of injection and the start of combustion. Ignition delay should be kept as short as possible, otherwise diesel knocking can occur if the delay is too long. Many works have shown that increasing fuel cetane number may shorten the ignition delay. In conjunction with the BPBT